Efeitos de seca prolongada na diversidade beta de assembleias de peixes de um reservatório semiárido - Pinheiro, Laura Amélia Pereira (Universidade Federal Rural do Semi-Árido, 2015)
The Santa Cruz reservoir suffered interferences in the reduction of the rain level between 2010 and 2014, where the precipitation values were under the expected level in that region, decreasing from 473 mm to 0 mm and resulting in the progressive reduction of the reservoir volume from 94% until 41.9%. So the objective of this study was: (1) test the effect of the reduction level of the water in the reservoir caused by the decreasing of the pluviosity above the beta diversity; (2) investigate spacial and temporal patterns of the beta diversity of the group using dissimilarity indexes based in incidences (β-sor) and abundance (β-bray); (3) investigate the importance of the turnover (β-sim) and nestedness (β-sne) components in the dissimilarities of Sorensen; (4) investigate the importance of the gradiente (β-gra) and balance (β-bal) components in the dissimilarity of Bray-Curtis; (5) evaluate the relations between the measures and components of dissimilarity and the dried gradients (reduction of the water volume and the monthly rains) and longitudinal (gradient dam-river) where the dissimilarities of Sorensen were calculated and so partitioned in components of turnover and nestedness, and also the Bray-Curtis dissimilarity partitioned in components of ballance and gradiente. To evaluate the correlation between the dissimilarity matrix and the dam-river gradient with the dry gradients, it was made multiples regressions in the distance matrix. The average value of the β-sor dissimilarity was from 0.44± 0.15 varying from 0 to 1. The β-sim values shows 56% of β-sor (p=0.001) while the β-sne was 1.4% (p=0.01). The average value of the Bray Curtis dissimilarities was from 0.70± 0.17 varying from 0.09 to 1. The β-bal value shows 12% (p=0.01), where the β-gra value shows 14% (p=0.01). The β-sor matrix was negatively correlated with the pluviosity, however the same was positively correlated with the reservoir volume. The β-sim matrix was negatively correlated with the pluviosity and with the volume of the reservoir while the same was positively correlated with the points distance. The β-sne matrix was positively correlated only with the distance matrix of the points. The β-bray matrix was positively correlated with the distance of the points and the reservoir s volume. The β-bal matrix was negatively correlated with the distances of the points and the pluviosity, while the same was positively correlated with the reservoir s volume. The β-gra matrix was positively correlated with the distance. This research revealed that the dry gradient changes the ecosystem of a tropical reservoir, principally by the turnover of the species and the abundance gradient.
prolonged drought effects on beta diversity of fish assemblages of a semiarid reservoir
Keywords: Storage and conservation of water; Reservoir Santa Cruz - RN; Dissimilarity; climate change; Ecosystem - tropical reservoir; Armazenagem e conservação de água; Reservatório de Santa Cruz - RN; Dissimilaridade; Mudança climática; Ecossistema - reservatório tropical; CIENCIAS AGRARIAS::MEDICINA VETERINARIA